1998
DOI: 10.1126/science.281.5379.1009
|View full text |Cite|
|
Sign up to set email alerts
|

BRCA1 Required for Transcription-Coupled Repair of Oxidative DNA Damage

Abstract: The breast and ovarian cancer susceptibility gene BRCA1 encodes a zinc finger protein of unknown function. Association of the BRCA1 protein with the DNA repair protein Rad51 and changes in the phosphorylation and cellular localization of the protein after exposure to DNA-damaging agents are consistent with a role for BRCA1 in DNA repair. Here, it is shown that mouse embryonic stem cells deficient in BRCA1 are defective in the ability to carry out transcription-coupled repair of oxidative DNA damage, and are hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
290
1
8

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(308 citation statements)
references
References 23 publications
9
290
1
8
Order By: Relevance
“…In an investigation of oxidative damage repair in cells with BRCA1 mutations, an increase in damage was found in homozygous but not heterozygous mutated cells. 1 In addition, mouse embryos engineered for homozygous BRCA2 mutations displayed radiosensitivity, whereas embryos with heterozygous mutations did not. 2 There are a number of possible reasons for the disparity between our results and these previously reported data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an investigation of oxidative damage repair in cells with BRCA1 mutations, an increase in damage was found in homozygous but not heterozygous mutated cells. 1 In addition, mouse embryos engineered for homozygous BRCA2 mutations displayed radiosensitivity, whereas embryos with heterozygous mutations did not. 2 There are a number of possible reasons for the disparity between our results and these previously reported data.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and in vitro studies suggest that homozygous mutations in either BRCA1 or BRCA2 result in a deficiency in processing of DNA damage repair and radiosensitivity. 1,2 Whether individuals heterozygous for a BRCA1 or BRCA2 mutation exhibit impaired recognition and processing of DNA damage is unknown. This is a relevant question for the management of individuals with a germline BRCA mutation, in that a deficiency in cellular DNA damage repair could increase the risk of a normal tissue injury following ionizing radiation or increase the risk of radiation-induced breast carcinogenesis.…”
mentioning
confidence: 99%
“…Subsequent studies have documented roles for BRCA1 in two highly specialized DNA repair processes: (1) transcription coupled DNA repair (TCR); and (2) homology-directed repair (HDR). Studies of both Brca1 À/À mouse embryo fibroblasts (MEFs) and a human breast cancer cell line (HCC1937) that contains a single mutant BRCA1 allele (5682insC) revealed that BRCA1 deficient cells have a defect in TCR of oxidative DNA damage caused by ionizing radiation (Gowen et al, 1998;Abbott et al, 1999). Thus, when strand-specific DNA repair was evaluated for several genes, including DHFR (dihydrofolate reductase), BRCA1 competent cells exhibited greater ability to repair the transcribed strand than the non-transcribed strand; whereas BRCA1 deficient cells showed equal repair of both strands, with a reduced rate of repair of the transcribed strand, as compared with BRCA1 competent cells.…”
Section: Functional Activities Of Brca1 Cell Cycle Regulation and Gromentioning
confidence: 99%
“…BRCA1 protein has been demonstrated to respond to DNA damaging agents by increased phosphorylation and movement out of nuclear dot structures Gowen et al, 1998;Scully et al, 1997a). To test whether proteins expressed from the TgN´BRCA1-B transgene respond to DNA damaging agents, we isolated fresh tissues and exposed them to ionizing radiation for various time periods.…”
Section: Placement Of a Brcamentioning
confidence: 99%